Paradigms of political change--Luther, Frederick II, and Bismarck : the GDR on its way to German unity - Brinks, Jan Herman (Marquette studies in philosophy, 2001)
This history of East German historiography traces the way historical studies in the German Democratic Republic interpreted and reinterpreted German nation building through the figures of Martin Luther, Frederick II, and Otto Bismarck. The author pays particular attention to the tension between portraying a German national identity while at the same time proclaiming a distinct GDR identity. He identifies three distinct periods of GDR historiography. Immediately after the war, Germany was seen as tragically not developed democratic institutions. This was soon followed by a theory of German history that identified a dialectic between progressive forces and reactionary figures represented by the three subjects of the study. The final period rehabilitated all three to certain extent, suggesting they were necessary parts of the "early bourgeois revolution." The author relates all three of these phases to the changing ideological needs of the East German state. Translated from the original German work DDR zwischen Einheit und Abgrenzung. Annotation copyrighted by Book News, Inc., Portland, OR.